Estudo dos efeitos cardiovasculares e renais do composto de rutênio FOR811A em ratos normotensos - Barbosa, Francisco Wendell Xavier (2021)
Hemodynamics is the functional study of blood in the mechanics of the heart and inside vascular structures. NO, in turn, is an essential signaling molecule, being the main responsible for the maintenance of vascular homeostasis in endothelial cells. On the other hand, nitric oxide donors are a class of drugs, still used today in the clinic, usually in cases of hypertensive crisis and severe heart failure. Due to the disadvantages of existing NO donors, as well as the advantages in the use of metals, nitrosyl-ruthenium complexes have been studied in recent years, these being potential NO donors and activators / stimulators of GCs, capable of promoting vascular relaxation. In addition, previous studies with FOR811A in isolated rat aortic rings, showed that the metal compound was able to reverse 100% of the pre-contractions performed in the vessels using phenylephrine, and also showed potential nephroprotective effects. All considered, this investigation aimed to study the cardiovascular and renal changes promoted by the ruthenium complex FOR811A, in normotensive rats. The experiments were carried out under protocol number 03120619-0, accepted by the UFC CEUA-NPDM. Male rats Wistar (250-300g) were used, divided into control group and FOR811A group (metalcompound at concentrations of 0.75; 1.5 and 3 mg/kg/mL, i.v.).The rats were anesthetized with ketamine (90 mg/kg) and xylazine (9 mg/kg, i.p.). Next, a SPR671 Mikro-tip pressure catheter was inserted in the abdominal aorta, to measure blood pressure; and a SPR868 pressure-volume Mikro-Tip catheter in the left ventricle, to measure the other cardiovascular parameters. FOR811A and the control solution were administered through a polyethylene cannula placed in the left femoral vein. Hemodynamic parameters were determined in the LabChart v8.0.1 system, using the PV loop module. Were also performed Nitrite/nitrate measurements in plasma, heart, kidney and liver, and histological analysis of kidney. For the statistical analysis, was used the Kolmogorov-Smirnov in order to verify the normality of the distribution. Descriptive statistics was performed using the calculations of mean and standard deviation, and two-way ANOVA, along with the Sidak test, were used to make the multiple comparisons between groups and doses. To do the data analysis, the GraphPad® Prism v8.0 software was used, with a statistical significance value set at p<0.05. FOR811A caused a reduction in initial systolic blood pressure (p<0.05) at a dose of 3 mg/kg/mL when compared to the dose of the control group, and also a significant reduction when compared to the baseline data collection of its own group (p<0.05). The metal compoundcaused a reduction in the initial dP/dt max (p<0.05), indicating a reduction in ventricular contractility. The nitrite dosage showed a significant increase in the plasma of animals that received FOR811A (p<0.05). Therefore, the ruthenium complex presented itself as a hypotensive agent, and also, the other cardiovascular alterations caused by it, are consistent with it being a NO donor.